Factors that influence employee loyalty: A Study at Manufacturing Sector in Klang and Shah Alam Industrial Zone / Haina Ismail and Fadilah Puteh - Ismail, Haina; Puteh, Fadilah (2021)
Employees are among the most important assets in any organization because they drive the organization's success or failure. It is critical to maintaining their loyalty to the organization while also preventing them from actively seeking another job alternative or opportunities at another organization (Murali, Poddar & Seema, 2017). Murali, Poddar, and Seema (2017) stated that in general, loyalty is defined as a person's devotion or sentiment of attachment to a specific object, which could be another person or a group of people, an idea, a duty, or a cause. According to Safra (2017), the term loyalty expresses itself in both thought and action and strives for the identification of the loyal person's interests with those of the object. Loyalty can come not only from the employee but also from the organization towards the employee. Jigjiddorj, Tsogbadrakh, Choijil, and Zanabazar (2019), stated that one of the most important factors in sustaining an organization's performance is the retention of skilled and experienced employees. Employee loyalty signals employees' or staff members' capacity to stay and contribute successfully to their employment for an extended period.